Four sexually transmitted diseases in one: a rare case report - Fernandes, S. D.; Jegadish, N.; Ramachandran, R.; Gopalakrishnan, K.; Narasimhan, Murali (International Journal of Research in Dermatology, 2020)
Sexually transmitted diseases (STDs) often pose a diagnostic challenge especially in countries like India, where access to reliable diagnostic laboratory tests is minimal. The exact cause of the STDs has to be determined, so that appropriate therapy can be administered and the risk of transmission to others can be reduced. However, determining the etiology can be complicated by limitations of current diagnostic testing modalities and by the fact that more than one infection may coexist. Here, authors report a case who presented with genital ulcer disease and discharge with four etiologies.